Perception of Media Coverage of MohBad’s Death among Youths in Benin City - Nwaoboli, Precious Emeke (Covenant Journal of Communication, 2025)
This study was an examination on the perception of media coverage of MohBad’s death among youths in Benin City. The objectives were to examine the exposure, perception and assessment of Benin youth to media coverage of MohBad’s death. Moored on the Perception theory, the researcher utilised survey as design and questionnaire as instrument of data collection. The population of the study was 568,719 while the sample size was 384.Findings showed that Benin youth were highly exposed to media coverage of MohBad’s death, primarily through new media platforms. More so, majority of the youth perceive the coverage as objective, accurate, informative and empathetic, however, there were also perceptions of bias, sensationalism, speculation and exploitation. Based on the findings, it was recommended, among other things, that media outlets should prioritise responsible reporting by ensuring objectivity, accuracy and avoiding sensationalism. They should also establish guidelines and ethical standards to maintain credibility and trust among youth consumers. Training programmes for journalists can be implemented to enhance their understanding of the impact of their reporting on youths’ perceptions.